Using Controlled Shunt Reactors for Voltage Stabilization on the Example of Real Electric Power System; IOP Conference Series: Materials Science and Engineering; Vol. 93: Modern Technique and Technologies (MTT'2015) - Gusev A. S. Alexander Sergeevich (Power industry, 2015)
Title screen